Bommies away! Logistics and early effects of repositioning 400 tonnes of displaced coral colonies following cyclone impacts on the Great Barrier Reef. (28th June 2019) - McLeod, Ian M.; Williamson, David H.; Taylor, Sascha; Srinivasan, Maya; Read, Mark; Boxer, Craig; Mattocks, Neil; Ceccarelli, Daniela M.
Summary: For over 40 years, management of the Great Barrier Reef Marine Park (GBRMP) in Australia has focused on limiting human‐use impacts to facilitate natural resilience and recovery. Compounding acute disturbances and chronic stressors have resulted in degradation of coral reef habitats in many areas of the Marine Park. Given current trends and predictions of escalating climate‐driven disturbances, it is increasingly evident that effective management of the GBRMP requires adaptive and novel approaches to protect and restore coral reef health. Here, we provide an overview of the logistical requirements and early‐stage ecological benefits of repositioning 400 tonnes of moderately sized (1–3 m diameter) Porites spp. coral colonies (bommies) that were displaced by cyclone‐generated swells that impacted reefs in the Whitsunday Islands during March 2017. An ecological survey conducted 16 months after the bommie repositioning revealed that several genera of hard coral had settled onto the bommies and that a range of reef fish species were associating with the restored habitat. Early findings suggest that the repositioning of the displaced bommies has assisted in restoring reef habitat structure and settlement habitat for juvenile corals, while improving natural aesthetics, vessel access and tourist experiences at Manta Ray Bay.